Carbon dots for real-time colorimetric/fluorescent dual-mode sensing ClO−/GSH. (October 2022) - Li, Huiqing; Wei, Zhenni; Zuo, Xianwei; Chen, Hongli; Ren, Cuiling; Dong, Yalei; Chen, Xingguo
Abstract: Hypochlorite (ClO − ) and antioxidants have been reported closely correlated with oxidative stress and related diseases. In recent years, many probes, especially fluorescent and colorimetric probes, have been developed to detect ClO − and antioxidants. It is meaningful to develop probes which can be used to detect them in these two modes. Herein, a novel dual mode carbon dots (DM-CDs) which can rapidly respond to ClO − and antioxidants by both fluorescent and colorimetric mode were synthesized. GSH was chosen as model antioxidants to evaluate its detection performance. The fluorescence of DM-CDs can be quenched by ClO − and then recovered by GSH, so sensitive and accurate detection of ClO − and GSH can be achieved. Meanwhile, the colour variation of this system can be observed by naked eye and detected quantitatively by UV–Vis spectra. The excellent analytical performance of DM-CDs together with their good biocompatibility endow them with great feasibility in cell imaging and real-time detection of intracellular ClO − and GSH. Graphical abstract: Image 1 Highlights: An effective, sensitive, and selective dual mode (colorimetric/fluorescent) sensor was synthesized for ClO ‾ and GSH. The rapidly respond of DM-CDs to ClO ‾ and antioxidants make it can be used in real-time detection. The excellent analytical performance and biocompatibility endow·DM-CDs can be used in cell imaging and real-time detection of ClO‾ and GSH.